2010
DOI: 10.1007/s10620-010-1477-x
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Model to Predict Advanced Fibrosis in Chronic Hepatitis B Virus-Infected Patients with High Viral Load and Normal or Minimally Raised ALT

Abstract: Background/Aims Treating a group of chronic hepatitis B virus (HBV)-infected patients with high viral load and advanced fibrosis or cirrhosis, regardless of their serum alanine aminotransferase (ALT) levels, is recommended. The aim of this study was to derive and validate a model to predict advanced fibrosis in a cohort of patients with viral replication and normal or minimally raised ALT [ALT \ 2 9 upper normal limit (UNL)]. Methods Information was collected from 124 patients who underwent liver biopsy. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…A number of studies have explored the feasibility of using non-invasive tests to predict cirrhosis. These include the Fibroscan and FibroTest-ActiTest, galactose and methacetin breath tests, TE, fibrotest, cirrhosis discriminant score, AST/ALT ratio, APRI, FIB-4 and AP index (24)(25)(26)(27)(28)(29). However, certain tests are impractical to use in a clinical setting since they require expensive instrumentation or may use less common biochemical markers, including α2-macroglobulin, haptoglobin and apolipoprotein A1, or the use of specialized software for computations.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have explored the feasibility of using non-invasive tests to predict cirrhosis. These include the Fibroscan and FibroTest-ActiTest, galactose and methacetin breath tests, TE, fibrotest, cirrhosis discriminant score, AST/ALT ratio, APRI, FIB-4 and AP index (24)(25)(26)(27)(28)(29). However, certain tests are impractical to use in a clinical setting since they require expensive instrumentation or may use less common biochemical markers, including α2-macroglobulin, haptoglobin and apolipoprotein A1, or the use of specialized software for computations.…”
Section: Discussionmentioning
confidence: 99%
“…Park et al [ 49 ] derived and validated a simple model of advanced fibrosis in patients with high viral load (HBV DNA) and elevated ALT, finding that age and AST were independent predictors of advanced fibrosis and sufficient to advise physicians about whether or not to perform liver biopsy. Kim et al [ 51 ] evaluated various serum markers, finding that APRI was the most useful for predicting significant fibrosis, and that the cirrhosis discriminant score (CDS) was the most useful for predicting extensive fibrosis. Comparison of hyaluronic acid, galactose and methacetin breath tests, APRI, FibroTest and FIB-4 showed that all were able to distinguish between mild and moderate fibrosis and cirrhotic and non-cirrhotic patients, but not all were useful as single tests while combinations of tests increased accuracy [ 52 ].…”
Section: Discussionmentioning
confidence: 99%